Rare, threatened, and endemic plants from the mountaintops of the Meridional Espinhaço Range (Revista Espinhaço, 2023)
Mountaintops are often refugia for vegetation because they are generally isolated islands distinct from the surrounding vegetation, often harboring rare and endemic species. In recent years, many rare species that were once thought to be extinct or on the brink of extinction have been rediscovered in mountain regions. This is the case with the species presented here, which were rediscovered after decades, or were previously unknown to science. Ongoing floristic studies in peatlands areas in Chapada do Couto have revealed the existence of six rare species of Eriocaulaceae, endemic from the Espinhaço Meridional and associated with wet ecosystems. Two species belong to Actinocephalus genus and four belong to Paepalanthus genus, including one rediscovered and two species still unknown to science. Given the rarity of their occurrences, the high degree of endemism, and the fragility of the ecosystems of mountaintops, the conservation status of these species is presented, along with comments on their morphology, geographical distribution, and photos of each of the species.
Keywords: Campos rupestres; Chapada do Couto; Conservation; Eriocaulaceae; Peatlands